National Security of China in the Context of Military and Political Threats in the Asia-Pacific Region - Dubrovskiy, Ivan R. (Конфликтология / nota bene, 2025)
The present study is devoted to analyzing the military-political confrontation between the People's Republic of China and the United States of America in the Indo-Pacific region. The focus is on Washington's strategic approaches to deter China, the expansion of the U.S. military presence, the development of new operational concepts, the strengthening of alliance ties, and the deployment of missile systems near Chinese borders. Simultaneously, China's countermeasures aimed at mitigating threats from the U.S. are examined, including the modernization of the People's Liberation Army of China (PLA), the development of reconnaissance and command systems, electronic warfare, space technologies, and missile armaments. Special attention is given to the perception of these processes in Chinese state and expert sources and their influence on the formation of a stable atmosphere of strategic rivalry that sets long-term parameters for regional security. The study is based on the analysis of publications from Chinese state media, military documents, expert assessments, and a comparative examination of American and Chinese strategic concepts. The scientific novelty of the research lies in the comprehensive consideration of the interaction between the two largest world powers in the Indo-Pacific region through the lens of Chinese evaluations and strategic documents. Unlike most existing works, the focus is on China's perception of threats and specific countermeasures taken by the PLA. It is shown that the U.S. views the strategy of deterring China as a priority, strengthening alliances and operational capabilities, while Beijing seeks to deprive Washington of advantages through asymmetric means, including missile forces, C4ISR systems, and electronic warfare. The conclusion is drawn that the emerging dynamics of military rivalry lead to increased strategic distrust, heightening the risk of escalation, and in the absence of crisis management mechanisms, could turn the Indo-Pacific region into one of the key areas of confrontation in the 21st century.